Pengaruh Kecerdasan Emosi dan Dukungan Keluarga terhadap Stres Akademik Siswa SMP Masa Pandemi - Muhammad Iwa Sanbada (Fakultas Psikologi Universitas Borobudur, 2023)
Stundent’s demand and duty in education case goes on, added to this unpredictable condition and situation cause covid-19 so that does’nt rule out possibility of causing psychological problems to student one of them is academic stress. Academic stress can be minimalized with the support form student’s environment, one of them is family support. However not only the outside factors which needed for decreasing academic stress, inside factors also needed so can be able to confront various demands and changes, that factor is emotional intellegent. The purpose of this research is to observe the effect between emotional intelligence and family support against student academic stress of SMPN 2 Kauman. This research used quantitatife approach with causal-comparative method and number of respondents were 177 students. The used Sampling technique was random sampling. R-Square value is 7.5%. Hypothetis test used multiple linear regression analysis which produced value sig.= 0.001<0.05 and f count (7.221) > f table (3.05) that mean there was an effect between emotional intelligence and family support againts student’s academic stress simultaneously. Emotional intelligent variable in t test get value sig. 0.021 < 0.05 and t table (1.973) > t count (-2.328) while family support variable in t test get value sig. 0.165 > 0.05 and t table (1.973) > t count (-1.394) that’s means emotional intteligent can affect student academic stress partially,however there isn’t with family support